The Oxford handbook of sociology and organization studies classical foundations - Adler, Paul S. (Oxford : Oxford University Press, 2009)
We live in a society of organisations, organisations which have profound and pervasive effects on our lives at work and beyond. Contemporary society and its organisations are in a period of accelerated, profound change. In this book, leading sociology and organsational scholars consider how 'classic' sociologists can help make sense of change.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Organizational sociology